A chloroplast envelope membrane protein containing a putative LrgB domain related to the control of bacterial death and lysis is required for chloroplast development in Arabidopsis thaliana - Yang, Yanjun (The New phytologist, 2012)
© 2011 The Authors. New Phytologist © 2011 New Phytologist Trust.